2019
DOI: 10.1186/s40249-019-0604-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants of distribution of freshwater snails and trematode infection in the Omo Gibe River Basin, southwest Ethiopia

Abstract: BackgroundDetermination of infection rates of snail populations is one of the basic tools for epidemiological studies of snail borne diseases. In this study, we opted to determine the trematode infection of freshwater snails in the Omo-Gibe River Basin, southwest Ethiopia.MethodsWe collected snail samples from 130 observation sites in lakes, wetlands, rivers, reservoirs and irrigation canals surveyed during the dry season (March to May) in 2016. The snail samples were examined for trematode infections by cerca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 34 publications
5
27
1
Order By: Relevance
“…Our results showed a positive correlation between the distribution of gymnocephalus cercariae and the value of DO, while xiphidiocercariae distribution was negatively correlated with DO. Similar to our results, Mereta et al . (2019) reported a negative correlation between the prevalence of the xiphidiocercariae emerging from Lymnaea natalensis and water DO.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results showed a positive correlation between the distribution of gymnocephalus cercariae and the value of DO, while xiphidiocercariae distribution was negatively correlated with DO. Similar to our results, Mereta et al . (2019) reported a negative correlation between the prevalence of the xiphidiocercariae emerging from Lymnaea natalensis and water DO.…”
Section: Discussionsupporting
confidence: 94%
“…(2016) reported xiphidiocercariae as the most common type of cercariae (44.3 %) but from the snail Bulinus truncates at the irrigation canal in the East Nile, Khartoum, Sudan. In addition, Mereta et al . (2019) reported the highest infection rate of xiphidiocercariae (1.5 %) emerging from Lymnaea natalensis at wet land of Omo-Gibe River Basin, southwest Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As assessed using morphological methods, 546(49.4%) of the snails collected were putatively identi ed as B. pfeifferi, whereas 310(28.1%), 101(9.1%), and 147(13.3%) were identi ed as Bulinus spp., Lymnaea and Bivalve, respectively. This result is consistent with the malacological survey conducted in freshwater bodies, in Sanja, Northwest Ethiopia, during January and April, where B. pfeifferi were 150(97.4%) and 180(81.4%), respectively and also B. forskalii and L. natalensis (29) (44). The main reason for the variation here may be an increase in organic matter will increase the concentration of detritus and possibly the proliferation of algae that forms the diet of planorbid and prosobranch snails and prevalence of Schistosoma spp.…”
Section: Discussionsupporting
confidence: 90%
“…McKinney (2008) has suggested that diversities in species of invertebrates, amphibians, reptiles and mammals tend to be lower in extreme urbanization areas. Furthermore, the lack of certain anthropogenic activities, such as open-field defecation and urination, and a comparatively low proportion of livestock farming can lead to low trematode infection rates in freshwater snails (Mereta et al, 2019). Species diversity of snail faunas served as first-intermediate hosts may also reflect the low infection rate in this study.…”
Section: Discussionmentioning
confidence: 86%